Comparison of Optical Coherence Tomography Findings in Patients With Primary Open-angle Glaucoma and Parkinson Disease - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Purpose: To evaluate the peripapillary retinal nerve fiber layer (RNFL), ganglion cell complex, and macular thickness as well as their correlation with the severity of diseases. Materials and Methods: This is a cross-sectional study and comparing both eyes of 26 patients with primary open-angle glaucoma, 25 patients with Parkinson disease (PD), and 23 healthy subjects. RNFL, ganglion cell complex, and macular thickness were measured and analyzed with optical coherence tomography (OCT) in all cases and correlation with severity of the disease was assessed in PD group. Results: The mean RNFL of PD was significantly thinner compared with controls (P=0.002). In glaucoma group, the mean RNFL was significantly thinner (96.28+/-12.49 mm) than PD (105.43+/-13.45 mm) and the controls (113.75+/-8.53 mm) (P<0.001; P<0.001, respectively). The global loss volume (GLV) rates in the glaucoma and PD group were significantly higher than controls, respectively (P=0.006; P<0.001/P=0.002, P=0.013). However, the GLV rate was significantly lower in PD group compared with glaucoma group (P=0.001). There was no significant correlation between OCT measurements and disease duration or severity in the PD patients. Conclusions: Although RNFL thickness and GLV changes may show the ganglion cell loss in both disease but none of the OCT parameters are correlated with the severity of PD. OCT may help to reveal the ganglion cell damage but may not help in determination of severity during the clinical follow-up of PD patients.
Keywords: optical coherence tomography; neurodegenerative disorders; ganglion cell complex; FIBER LAYER THICKNESS; RETINAL THICKNESS; GANGLION-CELL; EVOKED-POTENTIALS; DOPAMINE; ELECTRORETINOGRAMS; IMPAIRMENT; DECREASES; APOPTOSIS